Master Plan Pengembangan Wisata Bukit Tulen Telase: Pengabdian Masyarakat di Desa Air Limau, Kecamatan Muntok, Kabupaten Bangka Barat, Provinsi Kepulauan Bangka Belitung - Rias Arasy Arung Mallangke; Nikasius Jonet Sinangjoyo; Hary Hermawan (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Tulen Telase Hill Tourism Development Master Plan. The development of the Bukit Tulen Telase tourist area in Air Limau Village, Muntok District, West Bangka Regency is very prospective. This article is the output of community service activities that aim to recommend the Masterplan as a reference for developing the Bukit Tulen Telase tourist area. By analyzing tourism potential, the team analyzed market aspects based on the potential of the Bukit Tulen Telase area. Then analyze tourism potential based on institutional studies, and provide recommendations for developing integrated tour packages. The implementation of community service is divided into several stages. The first stage is a literature review followed by secondary data collection. The second stage consists of a primary data survey, orientation, and focus group discussions. The third stage identifies regional development potentials, problems, and analyses, and the final stage is concept formulation and development strategy. The Bukit Tulen Telase area in West Bangka Regency has shown promise as a tourist destination. The development of the Bukit Tulen Telase area necessitates synergistic collaboration from multiple parties to strengthen and complement one another. Putting together integrated tour packages can be a form of synergistic collaboration.